Aligning the band gap of graphene nanoribbons by monomer doping - Bronner, Christopher; Stremlau, Stephan; Gille, Marie; Brauße, Felix; Haase, Anton; Hecht, Stefan; Tegeder, Petra (Angewandte Chemie. International edition, 2013)
A matter of doping: Graphene nanoribbons (GNRs) were generated through an on-surface bottom-up synthesis and selectively doped at their edges by introducing nitrogen atoms in the precursor monomers. While the size of the band gap of 2.8 eV remains almost unchanged upon N substitution, a linear shift of the band structure is observed and corresponds to n-type doping (see picture; CB=conduction band and VB=valence band).